2023
DOI: 10.1002/est2.520
|View full text |Cite
|
Sign up to set email alerts
|

Extreme cold‐weather battery thermal management for optimal electric vehicle performance

C. Ruhatiya,
Ruthvik Gandra,
P. Kondaiah
et al.

Abstract: Battery thermal management system (BTMS) may seem a very standard term, but it is the lifeline of an efficient battery pack module in various vehicles and standalone stationary energy storage systems. The majority of the available literature is aimed toward temperature optimization of batteries in hotter climatic conditions. The cold temperature‐related effects on battery packs have amplifying implications on the battery cycle life and operational capacity. The electric vehicles operating in cold temperature e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…Simulation studies are conducted, and the models using the multi‐physics approach with various designs of BTMS incorporating PCMs and the results of available PCMs for use in severe low ambient temperatures. It is revealed that organic mixture‐type PCMs are most suited for cold weather conditions 140 …”
Section: Recent Work Related To Organic and Inorganic Pcms With Heat ...mentioning
confidence: 99%
“…Simulation studies are conducted, and the models using the multi‐physics approach with various designs of BTMS incorporating PCMs and the results of available PCMs for use in severe low ambient temperatures. It is revealed that organic mixture‐type PCMs are most suited for cold weather conditions 140 …”
Section: Recent Work Related To Organic and Inorganic Pcms With Heat ...mentioning
confidence: 99%